Technical design of a new bone conduction implant (BCI) system. - Taghavi, Hamidreza; Håkansson, Bo; Reinfeldt, Sabine; Eeg-Olofsson, Måns; Jansson, Karl-Johan Fredén; Håkansson, Emil; Nasri, Bayan (International Journal of Audiology, 2015)
Objective:The objective of this study is to describe the technical design and verify the technical performance of a new bone conduction implant (BCI) system.Design:The BCI consists of an external audio processor and an implanted unit called the bridging bone conductor. These two units use an inductive link to communicate with each other through the intact skin in order to drive an implanted transducer.Study sample:In this study, the design of the full BCI system has been described and verified on a skull simulator and on real patients.Results:It was found that the maximum output force (peak 107 dB re 1 μN) of the BCI is robust for skin thickness range of 2–8 mm and that the total harmonic distortion is below 8% in the speech frequency range for 70 dB input sound pressure level. The current consumption is 7.5 mA, which corresponds to 5–7 days use with a single battery.Conclusions:This study shows that the BCI is a robust design that gives a sufficiently high output and an excellent sound quality for the hearing rehabilitation of indicated patients.